A Survey of the health needs of a rural community for the establishment of a hospital-based community health service by the daughters of charity in the Philippines - Borjal, Estelita R.
The growing concern of society to meet the health needs of the people particularly in the rural areas has led to the government's implementation of the restructured health care delivery system. The intensification of health services in the rural population has been conceived by the government as a partnership among government, church, and private agencies with an effective support from the community.{{{{The Daughters of Charity in the Philippines have long realized the need to render health services to the people particularly those who are neglected. In fact, St. Vincent de Paul, their founder, was the initiator of health services to the rural population in Chatillon-les Dombes, a medium-sized town in southern France, as early as 1617. The Daughters of Charity in the Philippines are desirous of making their contribution to this national plan of intensification of health services in the rural areas.{{{{Preliminary to the establishment of health services, a survey of the problems and needs of the community is necessasry. This study was conducted to determine the health needs of two rural communities and ascertain the possibility of utilizing the existing resources of the Daughters of Charity in the area. The researcher chose the two remote barangays of Tinangis and Curry in Pili, Camarines Sur as the pilot area. It is assumed that the findings of this study would be useful for planning health services not only for this area but for other remote areas as well. An exploratory study of the health needs of a rural community will likewise be a basis for wise investments of time, money and human resources on the part of the Daughters of Charity.{{{{The Review of Related Literature was focused on health programs which are either hospital-based or community-based. The ten health programs in the Philippines which are found in the provinces of Isabela, Pampanga, Cavite, Camarines Sur, Panay (Island), Negros Occidental, Negros Oriental, Samar, Leyte, Lanao delNorte and Bukidnon were studied. Health programs of other countries sponsored by the Daughters of Charity in depressed areas and mission countries were likewise studied. These health programs are operating in 35 countries from six continents namely, Africa, North America, Latin America, Asia, Europe and Oceania.{{{{Employing the exploratory survey technique through the use of questionnaire/interview schedule and ocular observation, the study gathered data about the actual health needs of a rural population. One hundred families were used as sample population for the two barangays. This represents 22.6 percent of the total population of 486 families. Each family was represented by one respondent, the wife (mother) ...
Thesis (Master of Arts in Nursing) -- Concordia College Graduate School of Nursing
Keywords: Community health services -- Philippines; Health services administration--Philippines.; Hygiene, Rural -- Philippines